ANALISIS KARAKTERISTIK MUZAKKI DAN TATA KELOLA LAZ TERHADAP MOTIVASI MEMBAYAR ZAKAT PENGHASILAN - Kiryanto Kiryanto; Villia Nikmatul Khasanah (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2013)
Zakat is not something new in the eyes of Muslims. Muslims really believe and believe that zakat is one of the pillars of Islam. Problems often arise in the community we are to whom Zakat should be given. More major distributed directly by muzakki to mustahiq, or otherwise through amil zakat. For that goal to be achieved in this research is to analyze the influence of Gender ¸ The Faith, Knowledge of Islam, Governance LAZ, and Income Level on Motivation Paying Zakat on LPDU Sultan Agung. The population in this study are all obligatory zakat (muzakki) who pay zakat on income with a pay cut. And the sample in this study is the individual obligation of zakat in LPDU Sultan Agung as many as 125 people. Then the selected sampling technique was purposive sampling analysis tool used is multiple regression analysis.The results obtained from this study is that it can be concluded that the test results influence the motivation Gender pay zakat suggests that Type klamin no significant effect on the motivation to pay zakat. While the results of testing the influence of level of faith, knowledge of islam, LAZ governance and motivation level of income to pay zakat indicates that the variable has positive and significant impact on motivation to pay zakat.